Comparative evaluation of hypoxia preconditioned serum (HPS) and platelet-rich plasma (PRP) on preadipocyte survival and adipogenic differentiation - Jiang, Jun; Martin, Michael; Röper, Lynn; Knoedler, Samuel; Steinbacher, Vincent; Alageel, Sarah; Hanschen, Marc; Kükrek, Haydar; Dornseifer, Ulf; Schilling, Arndt F.; Machens, Hans-Günther; Moog, Philipp (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionLipofilling is a widely used technique in plastic and reconstructive surgery, but its long-term success is often limited by unpredictable fat graft resorption. Optimizing the adipogenic environment through bioactive factors may enhance graft survival and volume retention. This study investigates the adipogenic potential of Hypoxia Preconditioned Serum (HPS) and Platelet-rich Plasma (PRP), in comparison to normal serum (NS).MethodsCytokine profiles of HPS, PRP, and NS from 10 donors were analyzed. Human preadipocytes (n = 3) were cultured with low (10%) and high (40%) concentrations of these secretomes. Proliferation, cytotoxicity (LDH assay), lipid droplet formation (Oil Red O staining), and gene expression (qPCR) of adipogenic markers (PPARgamma, C/EBPalpha, FABP4, Adiponectin, LPL) were assessed after 2 and 4 days.ResultsHPS contained significantly higher levels of Adiponectin, IGF-1, bFGF, VEGF-A, and PDGF-BB compared with PRP and NS, while Leptin was lower in HPS and PRP than in NS. All conditions increased proliferation on day 4, with the highest cell counts in NS-40%. No treatment-related cytotoxicity was observed. HPS-40% induced the strongest adipogenic differentiation, evidenced by increased lipid droplet formation and upregulation of all measured adipogenic genes by day 4.ConclusionThese findings suggest that HPS enhance the proliferation, survival, and differentiation of preadipocytes. Validation in in vivo models and clinical studies will be necessary to confirm its potential efficacy in enhancing graft survival and volume retention.